Optimization of Irrigation Amount and Nitrogen Rate of Drip-Fertigated Sugar Beet Based on Sugar Yield, Nitrogen Use Efficiency, and Critical Nitrogen Dilution Curve in the Arid Southern Xinjiang of China - Ying Wang; Fulai Yan; Junliang Fan; Fucang Zhang (Plants)
The critical nitrogen (N) dilution curve is widely used to diagnose crop N status, but no such model has been developed for sugar beet. This study evaluated the effects of irrigation amount and N rate on sugar yield, N use efficiency, and soil nitrate-N (NO3-N) residue of drip-fertigated sugar beet in the arid southern Xinjiang of China. A reliable N nutrition index (NNI) for sugar yield was also established based on a critical N dilution curve derived from the dry matter of sugar beet. A three-year field experiment was established with six N rates (25–480 kg N ha−1) and three irrigation levels based on crop evapotranspiration (ETc) (0.6, 0.8, and 1.0 ETc in 2019 and 2020, and 0.4, 0.6, and 0.8 ETc in 2021). Results showed that sugar yield and N uptake increased and then generally stabilized with increasing N rate, while N use efficiency decreased. Most soil NO3-N was mainly distributed in the 0–60 cm soil layer, but increasing irrigation amount reduced residual NO3-N in the 0–80 cm soil layer. Additionally, the established critical N dilution curve of sugar beet was considered stable (Normalized RMSE = 16.6%), and can be used to calculate plant N requirements and further N rates during sugar beet growth. The results indicated that the optimal NNI was 0.97 under 0.6 ETc for sugar yield production of sugar beet in this study. This study provides a basis for efficient water and N management in sugar beet production in arid and semi-arid regions globally.